Temporal Diversity and Abundance of Zooplankton from Miri Coastal Waters - Reymathi, Nadarajan (Universiti Malaysia Sarawak, (UNIMAS), 2019)
Zooplankton is an aquatic animal that drift passively with water movement as well as actively move in the water column of seas, freshwater and oceans. They play an important role in the marine food web as they transfer the organic energy that being produced by unicellular algae to the higher trophic level. Studies of zooplankton in Malaysian coastal waters is limited to the Peninsular. Furthermore, research on distribution and composition of zooplankton in Miri, Sarawak had not been documented properly. Therefore, this study is designed to determine the temporal diversity and abundance of zooplankton from Miri coastal waters. Water samples had been collected by the previous researcher from four locations along Miri coastal waters using 100μm mesh size of plankton net and preserved in 5% formalin. In the laboratory, zooplankton species identification and enumeration have been done with the aid of compound microscope. Paracalanus sp., Oithona sp. and nauplii were the dominant taxa. The estimation of zooplankton alpha and beta diversity ranged from 37 to 78 and 15% to 214% respectively. The maximum density of zooplankton was recorded 2981 x 103 ind/L (Paracalanus sp. ) in May 2017 and the minimum density for 7 other species was 2 x 103 ind/L. The zooplankton communities were comprised of 4 different phyla where Copepods were the most dominant group. The baseline data obtained during this study is hoped to shed lights on the temporal diversity and abundance of zooplankton in Miri coastal water.